Analysis of Elementary Teachers' Acceptance of Deep Learning Media for Natural and Social Sciences Materials on Google Site Using UTAUT - Timtim Siti Mariam; Yunus Abidin; Dede Tri Kurniawan (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
The purpose of this study is to examine the perceptions and acceptances of elementary school teachers of deep learning-based learning media for Natural and Social Sciences (IPAS), which was developed using Google Sites. The framework utilized is the Unified Theory of Acceptance and Use of Technology (UTAUT), which provides a foundation to examine the acceptance of technology through the technology user’s perspective. A total of 100 elementary school teachers in Bandung Regency became respondents by filling out an online questionnaire via Google Forms. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results of the study indicated that teachers' affective attachment to learning media had a positive and significant influence on the intention to use the media. In contrast, other factors such as performance expectations, social influences, and supporting conditions showed weak or even negative influences. These findings confirm that the adoption of learning technology at the elementary school level requires a more humanistic approach, with an emphasis on the emotional experience of users as the key to increasing effective acceptance of technology.